Interspecific Variation in Leaf Phenolics of Six Prosopis Species - Pancholy, Anjali; Jindal, S K; Singh, Manjit; Kackar, N L; Solanki, K R (Annals of Arid Zone, 2016)
Phenolics in leaf extracts of six Prosopis species viz. P. julifora, P. tamarugo, P. chilensis. P. alba. P. siliquestrum and P. cineraria were studied using two dimensional thin layer chromatography. Each species had a characteristic phenolic pattern. Maximum number of phenolic spots (16) was recorded in P. chilensis and P. siliquestrum and minimum number (9) was observed in P. cineraria. In total. there were 37 spots in all the species. The degree of similarity as indicated by number of common spots among different species was in close agreement with their classification based on morphological criteria and geographical distribution.